SPEARMAN'S RANK CORRELATION ANALYSIS METHOD TO IDENTIFY CHANGES IN THE GPA OF GRADUATES FROM THE 5TH BATCH OF THE TEACHING CAMPUS PROGRAM AT UNIVERSITAS BAKTI INDONESIA - Hermanto, Hermanto; Harliana, Harliana (TRANSPUBLIKA INTERNATIONAL RESEARCH IN EXACT SCIENCES, 2024)
This research uses data from graduate students who participated in the 5th Batch of the Teaching Campus Program at Bakti Indonesia University. The sample data used are the GPAs (Grade Point Averages) before and after participating in the program, which are processed by testing correlation analysis using the Spearman Rank method with the help of SPSS to determine the Spearman correlation coefficient (r_s) and manual calculation to determine the t_value that will be compared with t_(table )the result with a significance level of 0.01. The data shows that the GPA values before and after participating in the Teaching Campus program have a t_value ≥t_(table ), which is 5.9718 ≥ 2.807 at a significant level of 0.01 (two-tail test). Therefore, H_O is rejected, meaning there is a change in the GPAs of students who graduated from the 5th Batch of the Teaching Campus Program. Thus, students can improve their learning quality in facing problems in the field, as shown by the changes in GPA values before and after participating in the Teaching Campus program at Bakti Indonesia University.